2017
DOI: 10.3389/fmars.2017.00362
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing of Seagrass Leaf Area Index and Species: The Capability of a Model Inversion Method Assessed by Sensitivity Analysis and Hyperspectral Data of Florida Bay

Abstract: The capability for mapping two species of seagrass, Thalassia testudinium and Syringodium filiforme, by remote sensing using a physics based model inversion method was investigated. The model was based on a three-dimensional canopy model combined with a model for the overlying water column. The model included uncertainty propagation based on variation in leaf reflectances, canopy structure, water column properties, and the air-water interface. The uncertainty propagation enabled both a-priori predictive sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 51 publications
(88 reference statements)
1
33
0
Order By: Relevance
“…The LAI values measured in Elkhorn Slough are high compared to some of the tropical seagrass meadows in Florida and the Bahamas [3,4,33,60], and the beds are considered to be dense seagrass canopies where the underlying sediment is not generally visible. Recent modeling work has shown that the relationship between top of the canopy reflectance of light and LAI decreases exponentially with increasing LAI [4,11]. In other words, the color at the top of the canopy darkens rapidly with initially increases in LAI, but the canopy color "saturates" at some density of LAI ( Figure 4A).…”
Section: Field Characterization Of the Benthosmentioning
confidence: 94%
See 3 more Smart Citations
“…The LAI values measured in Elkhorn Slough are high compared to some of the tropical seagrass meadows in Florida and the Bahamas [3,4,33,60], and the beds are considered to be dense seagrass canopies where the underlying sediment is not generally visible. Recent modeling work has shown that the relationship between top of the canopy reflectance of light and LAI decreases exponentially with increasing LAI [4,11]. In other words, the color at the top of the canopy darkens rapidly with initially increases in LAI, but the canopy color "saturates" at some density of LAI ( Figure 4A).…”
Section: Field Characterization Of the Benthosmentioning
confidence: 94%
“…Chl a = e ln (P/0.06)/0.65 (11) The retrieval ultimately aims to determine benthic reflectance R b . It is important to constrain the range of possible R b spectra to avoid the intrinsic ambiguity between bottom reflectance and water properties following Thompson et al [56].…”
Section: Semi-analytical Inversion Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some investigators used pixel-based classifiers, for examples, the maximum likelihood classifier on the original spectral bands and the spectral indices [14], support vector machines on three sunglint-corrected spectral bands and a depth invariant index [8], classification trees on spectral index after simple atmospheric correction [18]. Some researchers mapped seagrass species by pixels using a physics based model inversion [19], or spectrum matching and look-up tables [10]. Other investigators used the object based image analysis (OBIA) with unsupervised classifier [17] or regression tree classifier [13].…”
Section: Introductionmentioning
confidence: 99%